Chemical and physical stability of selected drugs for aerosol therapy with Sirmione thermal water - Francesco Saverio Robustelli della Cuna; Carlo Sturani; Sarah Galfrè; Luisa Gervasio; Cristina Sottani; Elena Grignani (Open Journal of Chemistry - Peertechz Publications, 2021)
In this work, we investigated the chemical and physical stability of ambroxol, beclomethasone dipropionate, budesonide and N-acetylcysteine after dilution with Sirmione thermal water, stored in ampoules for aerosol, at room temperature. The chemical stability of all active drugs was evaluated by Ultra-High-Performance Liquid Chromatography tandem mass spectrometry (UHPLC/MS/MS). All samples were analyzed in triplicate at room temperature under normal fluorescent light at 0h, 1h, 6h, 12h, and 24 h. According to the Official Pharmacopoeia of the Italian Republic, the degradation of a molecule that exceeds more than 10% is considered unacceptable. After dilution with thermal water of Sirmione, ambroxol, beclomethasone dipropionate, budesonide, and N-acetylcysteine, were found to be physically stable over the entire study (degradation <3%) at room temperature without any loss of activity.